2021
DOI: 10.1021/acsapm.0c01225
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecane-Nanoemulsion-Doped Polyacrylamide Hydrogels

Abstract: Hydrogels are promising supports for nanoemulsion drops since the skeleton provides a physical barrier to coalescence and possibly a thermodynamic barrier to Ostwald ripening. How these factors play a role in the encapsulation of oil drops in polymer networks for drug-delivery applications is largely unknown, owing to the challenge of measuring in situ drop size and understanding the drop–hydrogel interface. In this study, the electrokinetic sonic amplitude of sodium dodecyl sulfate (SDS)-stabilized hexadecane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Such hydrogels readily transport small ions, as evidenced, for example, by the electrical conductivity of polyacrylic acid (anionic) hydrogels (Kuhn mesh sizes nm) being comparable to those of the electrolyte ions within (Adibnia, Afuwape & Hill 2020). Similar conclusions have been drawn from the conductivity of uncharged polyacrylamide gels containing charged surfactant and added salt ions (Afuwape & Hill 2021). For the highly charged polyacrylic acid hydrogels of Adibnia et al.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Such hydrogels readily transport small ions, as evidenced, for example, by the electrical conductivity of polyacrylic acid (anionic) hydrogels (Kuhn mesh sizes nm) being comparable to those of the electrolyte ions within (Adibnia, Afuwape & Hill 2020). Similar conclusions have been drawn from the conductivity of uncharged polyacrylamide gels containing charged surfactant and added salt ions (Afuwape & Hill 2021). For the highly charged polyacrylic acid hydrogels of Adibnia et al.…”
Section: Introductionsupporting
confidence: 78%
“…Rehydrating the dried polymer would fill the cavities with water/electrolyte, creating a microstructure with an enhanced hydrodynamic permeability and modified electrical conductivity. Such an approach was recently demonstrated, in part, by Afuwape & Hill (2021), who immobilized surfactant-stabilized hexadecane drops in polyacrylamide hydrogels. However, the droplets in these composites did not evaporate when subjected to drying at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…According to Einstein's formula, rigid passive fillers (embedded in an incompressible, linear elastic continuum) are expected to increase the stiffness of the parent hydrogel by a factor 1 5 /2 + when the filler volume fraction ϕ ≪ 1. 45 Moreover, as highlighted in the Introduction, many studies have demonstrated Laponite actively increasing the stiffness of N-isopropylacrylamide and acrylamide-based hydrogels. Indeed, although sample-to-sample variations tend to increase with decreasing hydrogel charge, some values of G with f AAc = 0 (uncharged hydrogels) are ≈5 kPa greater than G of the parent hydrogel, qualitatively consistent with literature cited in the Introduction.…”
Section: Reportedmentioning
confidence: 99%
“…Certain synthetic polymers have impressive mechanical properties, such as poly(ethylene glycol) [90][91][92], poly(vinyl alcohol) [93,94] and polyacrylamide [95]. However, the poor biological activity of these materials is not conducive to the adhesion of cells and tissues, greatly limiting their applications in TE.…”
Section: Introductionmentioning
confidence: 99%